The Effect of Credit Financing on Profitability PT Adira Dinamika Multi Finance Tbk with Receivables Turnover Ratio Analysis - Farman, Fanji; Maharani, Asyifa Ayu; Marlina, Dina (LPPM Universitas Sebelas April, 2024)
This study analyzes the receivable turnover ratio (RTO) and the average time spent to collect receivables (Average Collection Period - ACP) at PT Adira Dinamika Multi Finance Tbk (ADMF) during the period 2014 to 2018. The research method used is